2015
DOI: 10.1002/elps.201500446
|View full text |Cite
|
Sign up to set email alerts
|

N‐Glycosylation analysis of formalin fixed paraffin embedded samples by capillary electrophoresis

Abstract: In this study, N-linked glycans from intact, formalin treated and formalin fixed paraffin embedded (FFPE) standard glycoproteins, human serum and mouse tumor tissue samples were investigated in respect to their susceptibility for formaldehyde treatment mediated changes. FFPE samples were first deparaffinized, followed by solubilization in radioimmunoprecipitation assay buffer and treated with PNGase F for N-glycan release. The released glycans were labeled with a charged fluorophore and analyzed by capillary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Our previous work suggested that the FFPE treatment apparently did not affect the glycan moieties of glycoproteins . As a continuation of that work, the objective of this study was to extend the utilization of FFPE samples towards molecular glycopathology for global N‐glycosylation profiling and sequencing with exoglycosidase enzymes.…”
Section: Introductionmentioning
confidence: 92%
“…Our previous work suggested that the FFPE treatment apparently did not affect the glycan moieties of glycoproteins . As a continuation of that work, the objective of this study was to extend the utilization of FFPE samples towards molecular glycopathology for global N‐glycosylation profiling and sequencing with exoglycosidase enzymes.…”
Section: Introductionmentioning
confidence: 92%
“…CGE-LIF was used to identify possible protein N-glycosylation alterations due to FFPE. 163 The N-linked sugars of FFPE treated samples were released using PNGase F digestion. No significant changes were revealed in the N-glycome profile upon FFPE, indicating that global N-glycome analysis on the FFPE samples might be feasible.…”
Section: Applicationsmentioning
confidence: 99%
“…Everest-Dass and Briggs [104] developed a novel method using MALDI MSI on formalin- between the N-glycosylation patterns before and after the formalin fixation and paraffin embedding processes in all sample types examined. Thus, it was suggested that FFPE tissue samples could be readily utilized to discover disease related N-glycosylation changes at the molecular, cellular and tissue levels in prospective and retrospective studies [106].…”
Section: Glycomicsmentioning
confidence: 99%